Pembelajaran IPS sebagai Sarana Pengembangan Karakter Keberanian dalam Berpendapat di Sekolah Dasar - Darman Manda; Dyan Paramitha Darmayanti; Iqbal Arifin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social Studies (IPS) learning in elementary schools plays a strategic role not only in mastering social concepts but also in character development, including students' courage to express their opinions. This study aims to describe how IPS learning can foster the courage to express opinions by analyzing 44 relevant literature sources. The results of the study show that students' courage develops through a combination of active learning processes, the application of innovative pedagogical approaches, and the integration of character values in learning activities. Active learning models provide initial opportunities for students to gradually practice speaking, while innovative approaches such as cooperative learning, social projects, and the use of contextual media strengthen students' ability to argue and understand the reasons behind their opinions. The reinforcement of character values, especially tolerance, responsibility, and mutual respect, provides an emotional foundation that fosters a sense of security, enabling students to express their views. These findings confirm that creatively designed, participatory social studies learning can build the courage to express opinions sustainably. The implications of this study emphasize the importance of the teacher's role in creating a supportive classroom environment, providing space for balanced dialogue, and opening opportunities for further research to examine the effectiveness of specific learning models in developing